Pengaruh Persepsi Risiko Dan Kepercayaan Terhadap Minat Penggunaan Berkelanjutan Dompet Digital Dana (Studi Pada Pengguna Aplikasi Dompet Digital Dana Di Kota Bandung) - Septiani, Hesti; Muzayanah, Fety Nurlia (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of perceived risk and trust on continuance usage intention on DANA E-Wallet Application. The research method used was descriptive verification with a quantitative approach. The sample used in this study was 120 using non-probability sampling technique with purposive sampling. The data analysis technique used is multiple regression analysis with testing the hypothesis partially and simultaneously. testing assisted with the SPSS tool. The results of this study are that there is a partial effect of perceived risk having a positive and significant effect on continuance usage intention, trust has a positive and significant effect on continuance usage intention, Simultaneous hypothesis results on perceived risk and trust simultaneously have a significant effect on continuance usage intention. The ????2 test for perceived risk and trust on continuance usage intention is obtained by R Square of 0.856 meaning that 85.6% of continuance usage intention is influenced by these two variables, while 14.4% of continuance usage intention is influenced by other variables not examined in this study.